INVESTIGATION OF METROLOGICAL UNITS AS "NOTIONAL CONCEPT" IN ENGLISH (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
All patterns of the objective world are reflected in the categories of human  knowledge. The categories of modern man's thinking are the product of a long historical  development. Their content changes as a person's knowledge of objective reality  deepens [Panfilov 1971: 3].